2013
DOI: 10.1158/0008-5472.can-12-2731
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Tumor-Infiltrating Macrophages Decreases Tumor-Initiating Cells, Relieves Immunosuppression, and Improves Chemotherapeutic Responses

Abstract: Tumor-infiltrating immune cells can promote chemoresistance and metastatic spread in aggressive tumors. Consequently, the type and quality of immune responses present in the neoplastic stroma are highly predictive of patient outcome in several cancer types. In addition to host immune responses, intrinsic tumor cell activities that mimic stem cell properties have been linked to chemoresistance, metastatic dissemination and the induction of immune suppression. Cancer stem cells are far from a static cell populat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
746
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 837 publications
(774 citation statements)
references
References 46 publications
14
746
0
1
Order By: Relevance
“…16,18,22,23,25,[33][34][35][36] Early studies demonstrated a critical role of CSF-1R on tumor-associated macrophage (TAM) infiltration of spontaneous murine breast tumors and human breast cancer xenografts. These studies showed reduced angiogenesis and delayed tumor progression to metastasis upon depletion or inhibition of CSF-1R-expressing TAMs.…”
Section: Discussionmentioning
confidence: 99%
“…16,18,22,23,25,[33][34][35][36] Early studies demonstrated a critical role of CSF-1R on tumor-associated macrophage (TAM) infiltration of spontaneous murine breast tumors and human breast cancer xenografts. These studies showed reduced angiogenesis and delayed tumor progression to metastasis upon depletion or inhibition of CSF-1R-expressing TAMs.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, when paclitaxel is used with an inhibitor blocking TAM-derived cathepsins, the total lung metastatic burden of MMTV-PyMT mice is lowered [24]. In orthotopic pancreatic tumor transplants, blockade of TAMs and monocytes via CSF1R or CCR2 inhibitors synergizes with gemcitabine and paclitaxel to slow cancer growth and to reduce peritoneal metastasis [29]. Like TAMs in MMTV-PyMT mammary tumors [22], TAMs from these pancreatic tumor transplants suppress CD8 + T cell activation to foster chemoresistance [29].…”
Section: Innate Immune Cellsmentioning
confidence: 99%
“…In orthotopic pancreatic tumor transplants, blockade of TAMs and monocytes via CSF1R or CCR2 inhibitors synergizes with gemcitabine and paclitaxel to slow cancer growth and to reduce peritoneal metastasis [29]. Like TAMs in MMTV-PyMT mammary tumors [22], TAMs from these pancreatic tumor transplants suppress CD8 + T cell activation to foster chemoresistance [29]. Studies in xenograft tumor models using human breast cancer cell lines have also shown that CSF1 neutralization together with a triple chemotherapy modality (cyclophosphamide, methotrexate, and 5-FU) reverses chemoresistance [30].…”
Section: Innate Immune Cellsmentioning
confidence: 99%
See 2 more Smart Citations